Dietary glucosinolates derived isothiocyanates: chemical properties, metabolism and their potential in prevention of Alzheimer’s disease - Khan, Farhana; Joshi, Abhishek; Devkota, Hari Prasad; Subramaniyan, Vetriselvan; Kumarasamy, Vinoth; Arora, Jaya (Frontiers in Pharmacology, 2023)
Alzheimer's disease (AD) is the most prevalent form of dementia by faraffecting millions of people worldwide. It is a progressive, irreversible, and incurable neurodegenerative disorder that disrupts the synaptic communication between millions of neurons, resulting in neuronal death and functional loss due to the abnormal accumulation of two naturally occurring proteins, amyloid β (Aβ) outside and tau inside neurons. According to the 2018 World Alzheimer's Report, there is no single case of an Alzheimer's survivor; even 1 in 3 people die from AD, and it is a growing epidemic across the globe.Fruits and vegetables rich in glucosinolates (GLCs), the precursors of Iisothiocyanates (ITCs), [derivatives of glucosinolates (GLCs)] rich fruits and vegetables have long been known for their pharmacological properties and have recently attracted intense increased interest for the possible prevention and treatment of in neurodegenerative diseases. Epidemiological evidence from systematic research findings and clinical trials suggests that nutritional and functional dietary ITCs interfere with the molecular cascades of AD pathogenesis and prevent neurons from functional loss. This aim of this review is to explore the role of GLCs derived ICTs in various molecular mechanisms involved in the progression of AD and their potential in the prevention and treatment of AD. review addressesIt also covers the chemistry chemical diversity of ICTs and their detailed mechanisms of action as reported by various in vitro and in vivo studies. Further clinical studies are necessary to evaluate their pharmacokinetic parameters and effectiveness in humans. and metabolism and discusses the relationship between dietary GLCs derived ITCs and molecular cascades that beneficially attenuate the progression of AD. It also explored novel strategies to prevent disease onset and how this knowledge from experimental and clinical studies facilitates the development of more targeted prevention strategies with these two phytochemicals.